2009
DOI: 10.1186/1471-2105-10-s13-p6
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function analysis of flexible alignment regions in proteins

Abstract: BackgroundProtein structural alignment plays a key role in defining gold standards for a variety of bioinformatics applications. These include homology assessment, phylogenetic tree construction and multiple sequence alignment evaluation.Our recent findings [1] however showed that superposition methods are rather sensitive to structural variation. To sidestep the problem of alignment variability, golden standards are often derived from the more conserved and 'trusted' regions. It therefore remains unclear whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…There are several factors that influence variability in structural alignments. Pirovano et al [ 9 ] determined that certain types of folds (helices and coils) are usually observed in inconsistent alignment regions. Since this observation is at odds with currently used alignment strategies, more care should be taken in the development of new algorithms.…”
Section: Proceedingsmentioning
confidence: 99%
“…There are several factors that influence variability in structural alignments. Pirovano et al [ 9 ] determined that certain types of folds (helices and coils) are usually observed in inconsistent alignment regions. Since this observation is at odds with currently used alignment strategies, more care should be taken in the development of new algorithms.…”
Section: Proceedingsmentioning
confidence: 99%